Are business ethics and engineering ethics members of the same family? - Bowie, Norman E. (Journal of business ethics, 1985)
The thesis of the paper is that there are no important differences between problems in business ethics and problems in engineering ethics. The problems are both of the same logical type. What keeps this contention from being obvious is that many view engineers as professionals and business persons as nonprofessionals. If you accept the traditional definition of ‘professional’ neither engineering nor business qualify. If you adopt the attitudinal definition of a profession which I propose, both practitioners could be professionals. This thesis is then tested by applying it to six specific issues in business and/or engineering ethics.